The Application of Early Mobilization for Postoperative Pain Following a Cesarean Section at RSI PKU Muhammadiyah Pekajangan, Pekalongan Regency - Ani Wahyuni; Heny Prasetyorini (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Cesarean section deliveries involve major abdominal incisions that cause intense postoperative pain, often leading to prolonged immobilization, heightened anxiety, and delayed recovery. Non pharmacological nursing interventions are critical to optimize recovery and mitigate reliance on heavy opioid analgesics. This clinical study evaluates the efficacy of progressive early mobilization on postoperative pain intensity, psychological adaptation, and functional safety among peripartum patients. An empirical descriptive case study with a sequential pre test and post test approach was conducted at RSI PKU Muhammadiyah Pekajangan in April 2026, involving five purposively selected postpartum mothers. Pain severity was systematically measured using the standardized Visual Analog Scale before and after a staged physical mobility protocol. The structured mobilization framework induced a uniform reduction of exactly three units on the pain scale for every subject, successfully shifting the cohort from moderate or severe distress to mild pain classifications. Furthermore, excellent wound integrity, complete hemodynamic stability, and reduced kinesiophobia were observed throughout all functional milestones. Progressive early mobilization represents a highly effective, safe, and independent nursing intervention that accelerates functional independence and safely alleviates post cesarean discomfort.